الاجتهاد الفقهي بين الانقطاع والاستمرار: بحث في حكم تقليد المجتهد الميْت عند الأصوليين - أحمد غاوش (International Institute of Islamic Thought, 2013)
تُعالِج هذه الدراسة حكم تقليد المجتهد بعد موته ممّن جاء بعده، وهي مسألة أصولية تناولها بعض أهل الفقه في مصنّفاتهم الأصولية، فالتعرّض لهذه المسألة بالبحث؛ قديمًا وحديثًا، إمّا قليل نادر، وإمّا مختصر موجز. وللمسألة أبعاد وآثار في الفكر الفقهي المعاصر يلزم بيانها، لتسليط الضوء على الأفكار التي تكبِّل العقل الفقهي المسلِم، وتقعد به عن النهوض بواجب التجديد والاجتهاد؛ واستحداث القول فيما يُستجد على ساحة الأمة من قضايا ومسائل. وتضمّن البحث عرضاً لمذاهب أهل الأصول والفقه في هذه المسألة؛ وفاقاً وخلافاً، من مختلف المدارس الإسلامية، بما في ذلك: ذكر أدلّة كلّ فريق على ما اختاره ونادى به من المعقول والمنقول، ومناقشة الأدلّة وتقويمها، والموازنة بينها. The study addresses the ruling of following a mujtahid after his death. This issue is an usuli one discussed by scholars of Usul. While it has important aspects and consequences in contemporary juristic thought, it has rarely been discussed, or if discussed, only briefly. It is hoped that this discussion will shed light on some of the ideas that restrict Juristic Muslim mind, from carrying the task of renewal and Ijtihad on contemporary issues confronting the Muslim ummah. The study presents opinions of different scholars of fiqh and Usul on this issue, from different schools of thought, identifying arguments of each school, whether derived from text or reason, discussing and evaluating their opposing arguments.